Where have all the jihadists gone? The rise and mysterious fall of militant Islamist movements in Libya - Wolfram Lacher (Stiftung Wissenschaft und Politik (SWP), 2024)
Prevailing approaches to understanding Islamist mobilisation struggle to explain why militant Islamist movements in Libya initially spread rapidly after 2011 and then disappeared almost overnight. Their decline poses a puzzle for conventional analyses. Tactical choices, such as the search for protection or allies, fuelled both the rise and fall of militant Islamists. The tactical options that were in fact considered by conflict actors were also determined by social factors, such as relationships of trust they maintained and the social acceptance they enjoyed. The short-lived flourishing of militant Islamist movements can be understood as a fashion, among other things. Protagonists sought to socially demarcate themselves or to conform by superficially adopting Islamist rhetoric and aesthetics and then discarding them again. Analysing the dramatic decline of militant Islamist movements helps to understand the full range of motivations fuelling their rise. Social recognition has so far been overlooked as a motivation for armed mobilisation. The Libyan case shows that labels such as 'Islamists' and 'jihadists' need to be treated with extreme caution, particularly in the context of ongoing conflicts. External actors should first recognise that conflict parties deliberately misuse such categories, and second they should develop a precise understanding of the social environment in which militant Islamist movements operate.
Keywords: 320; Islamist; militant Islamists; Libya; Muammar al Gaddafi; Arab Spring; social recognition; social environment; jihadists; conflicts